EFFICIENCY MARKET HYPOTHESIS, RANDOM WALK THEORY, AND FINANCIAL RATIOS-STOCK RETURNS: A COMPARATIVE STUDY OF BANKS IN INDONESIA, INDIA, AND CHINA IN THE POST-COVID ERA - ADININGSIH, TRIANA EVA (BAKI (Berkala Akuntansi dan Keuangan Indonesia), 2023)
This research aims to analyze how financial ratios affect firm value, utilizing the Efficiency Market Hypothesis and Random Walk Theory for analysis. It focuses on banking sector companies listed on the Indonesia Stock Exchange (XIDX), India Stock Exchange (XBOM), and China Stock Exchange (XSHG) from 2022 to 2023. This quantitative study employs purposive sampling, resulting in 184 firm- year samples, with data gathered from annual reports. Regression analysis using SPSS version 26 is the chosen method. The findings suggest that India has the most efficient market, while Indonesia aligns with the random walk theory, indicating weaker market efficiency. Notably, variables like "Return on Average Equity" in Indonesia and India and "Impairment Loans to Equity" in India and China significantly impact stock returns. These varying influences underscore the importance of considering country-specific factors in stock return predictions. However, it's essential to acknowledge tha the models explain only a portion of the variance in the dependent variable.